Establishing principles of joint operation of belt conveyor drives in case of random slide deviations of their electric motors - Goncharov K.A. (Научно-технический вестник Брянского государственного университета)
The paper contains the results of the probabilistic modelling of joint operation of multidrive belt conveyors in case of their full load as well as without cargo. As a result, modelling demonstrates the need of additional reservation of drive power when designing multidrive belt conveyors. On the basis of the modelling, operational principles of joint operation of belt conveyors are established when there are random slide deviations of their engines. These deviations represent specific conditions of electric motors distribution between the drives as well as the influence features of their parameters on the distribution of the carrying and tractive belts.